Apartados: refúgio entre regras e fronteiras - Sousa, Suzyanne Valeska Maciel de (2020)
This research addresses the refugee issue through three levels, the international system, the State (Brazil) and the individual, according to the model of three images by Waltz (2004). The main purpose was to analyze how to define power relations between these places, based on the considerations of Certeau (1994). Hence, the works intends to examine the construction of the International Refugee Regime as a strategy, which takes places in a formal platform and presents a normative character, as well as problematizing the way in which the Regime is territorialized in Brazilian national current legislation. We also aim to understand the role of the refugee as a historical subject, whose power is categorized as tactic, as his/her behavior emerges from an informal place and is deemed a reaction or subversion by those in formal forum. In methodological terms, the study employed a qualitative approach, with bibliographic and documentary reviews. Besides, the research also conducted semi-structured oral interviews, based on Meihy (2005) and Meihy and Holanda (2015), with Venezuelan refugees hosted by non-profit organization SOS Aldeias Infantis, in João Pessoa-PB. Was recorded twelve interviewees, of which eleven were refugees and one was Aldeias SOS staff. The work allowed us to better understand how the relations among the three images work, with emphasis on the view of refugees and how it casts light on the new and important aspects about the assistance offered in Brazil.